Effects of in ovo administrated aflatoxin b1 on the embryonic development of proximal tibial growth plate in broiler chickens - Yasemin Öznurlu; İlhami Çelik (Eurasian Journal of Veterinary Sciences)
In this study, detrimental effects of in ovo given aflatoxin B, (AFB,) on the embryonic development of tibia and its proximal growth plate were determined by means of histologic and histometric methods. For this purpose, 1024 eggs of Hubbard parent stocks were divided into 10 groups, which designed as controls, drilled-sealed group, solvent group, 2,5 ng AFB,/egg group, 5 ng AFB1/egg group, 7.5 ng AFB,/egg group, 10 ng AFB,/egg group, 15 ng AFB,/egg group, 17.5 ng AF8,/egg group and 20 ng AFB,/egg group. Test solutions were injected via the air-sac at pre-incubation period. Five eggs from each group were opened at 13rd, 15lh, 17th, 19th, 21th day of incubation, and also at 1st and 2nd weeks of post hatch. At these periods, soft tissues were removed from the tibia, their length was measured with a measured with a digital callipers and following weighed. The relative tibia weights (g of tibia 100g-1 of embryos and chicks) were calculated The tibial tissue samples were processed for routine histological techniques. The results of tibial measurements have revealed that AFB, treated groups displayed lower mean tibial lengths and weights when compared to the drilled-sealed and solvent groups (P<0.05). Results ol the light microscopic investigations have showed that both proliferative and hypertrophic zones significantly (P<0.05) narrowed in all AFB, treated groups whereas, the transitional zone thickened in both 17.5 and 20 ng AFB, /egg groups when compared lo the controls, drilled-sealed and solvent groups. The results have revealed that in ovo given AFB1 at the doses of I7.5 AFB, /egg and 20 ng AFB, /egg might interfere and to cause retardation of embryonic development ol the skeletal system. The effects are more pronounced in tibia and its proximal growth plate.